1980
DOI: 10.1111/j.1365-2125.1980.tb01753.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of naproxen sodium and its relationship to clinical analgesic effects.

Abstract: 1 In the first of a series of trials with naproxen sodium it was shown that patients achieved significantly earlier and higher plasma levels of naproxen when naproxen sodium was administered. 2 In a second study comparing naproxen with naproxen sodium in patients with post‐partum pain, pain intensity was consistently lower for the group receiving naproxen sodium. However, statistically significant differences were not seen until 4 to 5 h after medication. 3 A final study documented that a more frequent dosage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(35 citation statements)
references
References 16 publications
1
34
0
Order By: Relevance
“…Pharmacokinetic differences between the formulations are restricted to the slightly earlier and higher plasma concentrations achieved with naproxen sodium, which result in a slightly faster onset of action; in other respects the 2 formulations are pharmacokinetically, pharmacologically, and therapeutically equivalent at comparable doses (38,48,52). Naproxen and naproxen sodium are generally considered to be efficacious, safe, and well tolerated in humans, although renal and gastrointestinal side effects similar to those observed with other NSAIDs are occasionally seen (15,18,52).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacokinetic differences between the formulations are restricted to the slightly earlier and higher plasma concentrations achieved with naproxen sodium, which result in a slightly faster onset of action; in other respects the 2 formulations are pharmacokinetically, pharmacologically, and therapeutically equivalent at comparable doses (38,48,52). Naproxen and naproxen sodium are generally considered to be efficacious, safe, and well tolerated in humans, although renal and gastrointestinal side effects similar to those observed with other NSAIDs are occasionally seen (15,18,52).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that higher BA and faster absorption may correspond to improved clinical benefit. 3,34) Furthermore, in addition to the in vivo animal experiments, our preliminary in vitro human cadaver skin permeation studies indicated that the MNs were feasible to deliver sufficient SS across the skin for treatment of migraine by increasing the diameter of the array up to 2 cm (data not shown). Therefore, although further practical verifications are needed, these findings demonstrated that the novel sodium hyaluronate MN delivery system was an excellent candidate for delivering SS to migraine patients, while avoiding the pain associated with use of hypodermic needles.…”
Section: Discussionmentioning
confidence: 99%
“…Naproxen ( Fig.1) chemically designated as [(S)-6-methoxy-alpha-methyl-2-naphthaleneacetic acid] is non-steroidal anti-inflammatory medicine that demonstrates both antipyretic and analgesic behavior [1][2][3][4]. It can be used for the remedy of various diseases, such as rheumatoid arthritis, juvenile rheumatoid arthritis, ankylosing spondylitis, osteoarthritis, primary dysmenorrheal and acute gout [5].…”
Section: -Introductionmentioning
confidence: 99%